Analysing the Factors that Influence Market Participation among Avocado Producers in Kaffa Zone of South-Western Ethiopia. Issue 1 (31st December 2022) - Gurmis, Nigus; Melese, Tsegaye
ABSTRACT: Market participation by smallholder farmers is crucial for livelihood improvement in developing countries. Even though it is the source of currency, the fruit market has not been given attention. Therefore, this study intended to identify factors influencing avocado producers' market participation decisions and volume of market participation in the Kaffa zone, Ethiopia. Gimbo and Chena districts were selected purposefully with a multi-stage sampling method on the bases of production potential. Data for this study were collected from 384 households from six representative Kebeles with the Cochran formula. Both primary and secondary data were employed. Primary data was collected using a semi-structured questionnaire. Both descriptive statistics and the double hurdle econometric model were employed for analysis. The descriptive statistics showed that out of 384 households (236 participants and 148 were non-participants), 89.19% were male avocado market participants and 76.69% were male avocado non-market participants. The econometric model results confirmed that market participation decisions (hurdle 1) of producers were significantly influenced by sex, market experience, education level, and family size. The intensity of avocado market participation (hurdle 2) is significantly affected by the market experience, access to credit services, extension contact, family size, and off-farm income. Understanding the factors of both avocado market participation decisions and level of participation helps policymakers to re-adjust their policies both at the regional and federal government levels. Then, this study recommends that governments need to exploit more effort into market-oriented production to enhance the productivity of avocados. Credit providers also must strengthen. Additionally, modern production technologies must be taken into consideration to increase the avocado quantity produced.